Burkitt lymphoma of the head and neck: An international collaborative study. (28th June 2021) - Arboleda, Lady Paola Aristizabal; Rodrigues‐Fernandes, Carla Isabelly; Mariz, Bruno Augusto Linhares Almeida; de Andrade, Bruno Augusto Benevenuto; Abrahão, Aline Corrêa; Agostini, Michelle; Romañach, Mário José; Pontes, Hélder Antônio Rebelo; Fonseca, Felipe Paiva; Robinson, Liam; van Heerden, Willie F. P.; Carlos, Román; et al.
Abstract: Background: Burkitt lymphoma (BL) is an aggressive B‐cell lymphoma with three variants (endemic, sporadic, and immunodeficiency‐associated), presenting with specific epidemiological and clinical features. Burkitt lymphoma affects the head and neck region (BLHN) in approximately 10% of cases. The aim of this study was to undertake a comparative analysis of the clinicopathologic and immunohistochemical (IHC) features of BLHN diagnosed in patients from Africa, Guatemala, and Brazil. Methods: Cases diagnosed as BLHN were collected from the files of six oral pathology laboratory services (Brazil, South Africa, and Guatemala) and one Brazilian pediatric oncology hospital from 1986 to 2020. Clinicopathological and IHC data, and Epstein‐Barr virus (EBV) status by in situ hybridization data for each case were reviewed and described. Results: Of the 52 cases, BLHN was predominant in pediatric patients [43 (82.69%)] and males [43 (82.69%)], with a mean age of 11.26 ± 9.68 years (range, 1‐39 years). Neck and cervical lymph nodes [14 (26.92%)], and involvement of both maxilla and mandible [8 (15.38%)], were the most common anatomical sites. Clinically, tumor/swelling [40 (31.25%)], cervical lymphadenopathy [14 (10.94%)], pain [12 (9.38%)], and bone destruction [12 (9.38%)] were frequent findings. All cases showed typical morphological characteristics of BL. IHC profiles included positivity for CD20 [52 (100%)], CD10 [38 (79.17%)], Bcl6 [29 (87.88%)], and c‐Myc protein [18 (81.82%)]. EBV was positive in 18 cases (62.07%). The Ki‐67 index ranged from 90 to 100%. Conclusion: The clinicopathological and EBV profile of BLHN in South African, Guatemalan, and Brazilian patients is similar.